Research of dynamics of endurance of boys 13-14 years, gettings busy in sporting section on football on the experimental program. - Tsaruk O.V; Tsaruk V.S (Kharkov National Pedagogical University, 2012)
Research purpose - experimentally to approve the program on development of endurance for boys in the process of employments by football. In an experiment took part boys 13-14 years in an amount 98 schoolboy. During pedagogical experiment it was improved and modern organization of work of school section is activated on football on two factors: by the change of maintenance of the program of work of section of football; by the improvement of old methods of physical education. The dynamics of endurance of boys is considered through research morphofunctional indexes, somatic health and their comparison in control and experimental groups. Efficiency of the inculcated program is well-proven in the after hours form of studies. It is resulted recommendation in relation to application of facilities of football for education of endurance on the lessons of physical culture.